2013
DOI: 10.1212/01.wnl.0000436937.32410.32
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptides and mortality after stroke

Abstract: BNPs are associated with poststroke mortality independent of NIH Stroke Scale score, age, and sex. However, their translation to clinical practice seems difficult because BNP/NT-proBNP add only minor predictive value to clinical information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
65
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 43 publications
(47 reference statements)
2
65
2
1
Order By: Relevance
“…Variability in biomarker measurement, particularly between sites, has been identified. For example, in a meta-analysis of IL-6 in stroke and another meta-analysis of BNP in ischemic stroke, >1000 fold difference in mean protein concentration was observed between sites 40, 41 . Reducing such variability will be essential to replicate promising biomarkers and biomarker panels in stroke.…”
Section: Molecules To Include In Biomarker Panels and Their Measurementmentioning
confidence: 99%
“…Variability in biomarker measurement, particularly between sites, has been identified. For example, in a meta-analysis of IL-6 in stroke and another meta-analysis of BNP in ischemic stroke, >1000 fold difference in mean protein concentration was observed between sites 40, 41 . Reducing such variability will be essential to replicate promising biomarkers and biomarker panels in stroke.…”
Section: Molecules To Include In Biomarker Panels and Their Measurementmentioning
confidence: 99%
“…Predicting stroke mortality is important in the management of patients with stroke and setting goals of care. A recent meta-analysis of 16 studies (3498 participants) evaluated the association of B-type natriuretic peptide (BNP) with stroke mortality and assessed whether adding this blood biomarker could improve clinical prediction of stroke mortality [3]. BNP or the inactive N-terminal fragment of BNP (NT-proBNP) was measured in ischemic and hemorrhagic strokes.…”
Section: Highlights From the Latest Articles In Biomarkers In Medicinementioning
confidence: 99%
“…Usually BNP is measured by this N-terminal fragment (NT-proBNP), since the Nterminal part seems to be more stable than BNP itself. Serum concentrations of NTproBNP are usually almost 10 fold higher than BNP concentrations; this is caused by differences in metabolism: the inactive fragment having a longer half-live (3).…”
mentioning
confidence: 99%
“…Elevated plasma levels of NT-proBNB and of troponin T are markers of future major cardiac events, but also are correlated with multiple other vascular conditions and risk factors, even with mortality from noncardiovascular causes (7) In neurovascular conditions, elevated plasma levels of BNP and NTproBNP predicts the risk for an incident ischemic stroke, predicts the risk for cardio-embolic etiology of a stroke, the risk of having a new onset AF episode in the setting of an ischemic stroke, the risk of death in the acute phase and the risk of poor functional recovery at 3 and 6 months after stroke. Generally, both BNP peptides have been associated with unfavorable clinical outcome and mortality in stroke patients (3) In a prospective epidemiological study (7) was shown that increased levels of natriuretic peptides were associated positively with stroke risk factors and with increase in total stroke incidence : the combination of both elevated troponin T and NT-proBNP tripled the risk of ischemic stroke. BNP predicts a high-risk vascular profile in general population, risk factors for stroke were prevalent in individuals with high BNP values (7).…”
mentioning
confidence: 99%